Front Metter SOCA. Vol.16, NO 1, January 2022 - Front Metter SOCA Vol.16, NO 1, January 2022 (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2022)
Front Metter SOCA. Vol.16, NO 1, January 2022